Conflicts of interest - Carson, Thomas L. (Journal of business ethics, 1994)
This paper has two distinct objectives. (1) I defend an analysis of the concept of a conflict of interest. On my analysis the concept of a conflict of interest is broader than is generally supposed. I argue that a very large class of cases not ordinarily regarded as conflicts of interest should be so regarded. Conflicts of interest are an integral feature of many professional relationships and do not (as is often supposed) require the existence of “external” financial or personal relationships. (2) I defend and explain the commonsense view that conflicts of interest areprima facie wrong and argue that in ordinary cases it is wrong, all things considered, to allow an avoidable conflict of interest to occur. I attempt to establish these claims on the basis of weak and relatively noncontroversial assumptions.